El culto al cristo crucificado. Una interpretación - Sanginés García, Esther (Universidad Michoacana de San Nicolás de Hidalgo., 2009)
The God is in the sacred cave, replica of the maternal uterus where the pilgrims penetrate that from the four cardinal points they arrive dancing. Conches, bells, flower and song they unite in the celebration of the ritual of the life in that he/she offers to Oztoteotl the beautiful blood so that it continues I live and the world persists. Suddenly the party is interrupted. The god of those Indians are reduced to pieces, their remains serve from footstool to Christ's image dead, bleeding, tortured whose miraculous appearance substitutes it in the altar. In the new temple, Christ's tormented face was penetrating for the view and the one tact until the same heart of the Indian culture, men, women and children got tied up emotionally to Jesús agony, of their hands the miraculous made statues came out of cane of corn, wooden, or I sweep; that they appeared in the sacred caves and they created a bridge among the twilight of a world that left with the old sun and the new era that he/she entered to the rhythm in that the men reverentemente kissed the body empapado' of bleed... The sacred thing you [he/she made]... present. 1. A new image, a new God, in the one break and the continuity of the memory, God is in the image to miracle appearance of the Mr. of Chalma in 1539, they continued him/her: the Mr. of the one Sacromonte or Mr. of the Saint Funeral (1541), the Mr. of Araró, the Sacred Christ of Otatitlán, the Mr. of the Works and several more. The first sanctuaries dedicated to the one Crucified Christ was founded in what today is Mexico, during the first century of the it conquers, in sacred places where it was worshipped to the Indian gods, in their biggest part, its origin owes to situations sobrenaturals., through them the enormous fervor was channeled religious of the Indians and two histories, two traditions were conjugated.

El Dios está en la cueva sagrada, réplica del útero materno donde penetran los peregrinos que desde los cuatro puntos cardinales llegan danzando. Caracolas, cascabeles, flor y canto se unen en la celebración del ritual de la vida en que se ofrece a Oztoteotl la sangre preciosa para que siga vivo y el mundo persista. De pronto la fiesta se interrumpe. El dios de los indios queda reducido a pedazos, sus restos sirven de escabel a una imagen de Cristo muerto, sangrante, torturado, cuya aparición milagrosa lo sustituye en el altar. En el nuevo templo, el rostro atormentado de Cristo fue penetrando por la vista y el tacto hasta el corazón mismo de la cultura india, hombres, mujeres y niños se ataron emocionalmente a la agonía de Jesús, de sus manos salían las estatuas milagrosas hechas de caña de maíz, de madera, o barro; que se aparecían en las cuevas sagradas y creaban un puente entre el crepúsculo de un mundo que se iba con el viejo sol y la nueva era que entraba al ritmo en que los hombres besaban ―reverentemente el cuerpo ̳empapado‘ de sangre... Lo santo se [hacía]... presente‖ 1. Una nueva imagen, un nuevo Dios, en el rompimiento y la continuidad de la memoria, Dios está en la imagen. A la ―milagrosa‖ aparición del Señor de Chalma en 1539, le siguieron: el Señor del Sacromonte o Señor del Santo Entierro (1541), el Señor de Araró, el Santo Cristo de Otatitlán, el Señor de los Trabajos y varios más. Los primeros santuarios dedicados al Cristo crucificado se fundaron en lo que hoy es México, durante el primer siglo de la conquista, en lugares sagrados donde se veneraba a los dioses indios, en su mayor parte, su origen se debe a situaciones ―sobrenaturales‖, a través de ellas se canalizó el enorme fervor religioso de los indios y se conjugaron dos historias, dos tradiciones.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; Religión; Interpretación; Representación; IIF-M-2009-0025; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/12